"Steakhouse Syndrome" pada Pasien Dewasa di RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar - Ni Made Ayu Dwipayanti; I Ketut Mariadi (MEDICINUS, 2026)
Esophageal obstruction by foreign body is a common emergency condition, third rank after upper and lower gastrointestinal bleeding. This condition may be life-threatening, depending on the type of ingested object, the location of the obstruction, the patient’s condition, and the time interval from the incident until the treatment is given. The annual incidence has been reported to be 13 per 100,000 of the general population. We report the case of a 30-year-old female patient who presented with difficulty swallowing for two days prior to hospital admission after eating beef steak. This complaint was accompanied by chest pain and a burning sensation. Examination revealed a patent airway, with no complications such as hematemesisor abnormal breath sounds. Upper gastrointestinal endoscopy showed a food blockage (a mass of insufficiently chewed steak) in the esophagus, located 20 cm from the teeth, with erosion of the surrounding mucosa. This location is consistentwith previous studies showing that, in adults, about 68% of obstructions occur in the distal esophagus, between the aortic arch and the lower esophageal sphincter (LES). In this case, no medications were administered to relax the smooth muscles of the LES. The steak was pushed from the esophagus into the stomach using endoscopy. The obstruction was successfully removed, and the patient’s symptoms resolved. In conclusion, the patient’s symptoms were caused by an acute steak mass, known as “steakhouse syndrome”.